Neonatal Intensive Care Unit Apocalypse—Rise of the World Health Organization Priority Pathogens - Apurva Kawdiya; Swati Bhalse; Gaurav Mogra; Kewal K Arora (Pediatric Infectious Disease)
Background: With higher neonatal survival, increasing neonatal intensive care unit (NICU) admissions, and rampant use of antibiotics, highly resistant organisms have become a major hurdle in the path of intact survival of neonates. In 2017, a list of World Health Organization (WHO) global priority pathogens (GPP) was released. Identifying the burden of these organisms in NICU will pave the way for devising further antibiotic strategies in their management. Aims and objectives: Primary objective was to study the burden of WHO GPPs and their antibiotic sensitivity pattern. Secondary objective was to assess their virulence by studying their outcome. Materials and methods: Retrospective data of positive blood cultures was collected for a period of 1.5 years (April 2022 to September 2023) from neonates admitted to the level three NICU of a medical college. Antibiotic sensitivity patterns and final outcome were noted. Results: A total of 105 positive blood cultures were analyzed. Of these, 64% (n = 68) amounted to WHO GPPs. These pathogens were more commonly associated with late-onset sepsis 63% (n = 43) and hence more likely to be nosocomial. Most of these (89%) were gram-negative. Of these, Klebsiella pneumoniae (carbapenem/third-generation cephalosporin-resistant) was the most commonly isolated organism found in 28% (n = 30). Colistin, tigecycline, and cotrimoxazole were some of the antibiotics to which these strains were sensitive variably. Acinetobacter baumannii (carbapenem-resistant) was found to be the most virulent, with a fatality rate of 62%. Among gram-positive organisms, Enterococcus faecium was found in five cases, and all were sensitive to linezolid and tigecycline. Conclusion: Burden of drug-resistant organisms in NICU is increasing at an alarming rate. They are not only difficult to treat but are also associated with poor outcomes. This study highlights the alarming increase of resistant organisms in the NICU.